The relationship between very high gravity fermentations and oxidative stress in the lager yeast Saccharomyces pastorianus - Mott, Alexander Charles (2017)
Very High Gravity fermentations are an increasingly attractive proposition within the brewing industry as a means of energy saving and optimising process efficiency. However, the use of very high gravity (>20°P) wort is associated with a range of biological stress factors. Ethanoic and osmotic stresses have been widely analysed along with oxidative stress in relation to propagation and early stage fermentation. The aim of this research was to investigate the impact of wort gravity on oxidative stress, and understand how this affects the plasma membrane at VHG. Finally the effect altered ergosterol content was analysed. The characteristics of Saccharomyces pastorianus strains were assessed for their ability to withstand the increased pressures of VHG (22°P) fermentations. VHG fermentations showed increase ethanol production at the expense of fermentation length, and increased ethanol production during VHG fermentations was offset by an increase in fermentation length. All fermentations were observed to accumulate ROS and increased antioxidant levels, with levels being furtherelevated in the VHG environment. Further analysis of S. pastorianus strains indicated that the levels of oxidative stress observed in fermentation had a negative effect on membrane fluidity and increased damage of the plasma membrane was observed. Analysis of ergosterol enriched yeast indicated that although fermentation rate was increased, a trade off with alcohol and biomass production was observed. Furthermore in response to oxidative stress, ergosterol enriched yeast showed reduced tolerance, decreased membrane fluidity and increased membrane damage. This work will give further insight into the response of lager yeast to oxidative stress present during VHG fermentations.